1994
DOI: 10.1111/j.1751-1097.1994.tb05046.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Benzoporphyrin Derivative in the Circulation of Mice Without Skin Photosensitivity

Abstract: In vitro experiments with benzoporphyrin derivative monoacid ring A (BPD) confirmed earlier studies that it was taken up rapidly (within 30 min) to maximum concentrations by all cells tested. It was also confirmed that rapidly dividing tumor cell lines and mitogen-activated murine T lymphocytes took up significantly more (5-10-fold) BPD than did normal splenic lymphocytes. Further experiments were undertaken to determine whether BPD could be activated by whole-body irradiation with red light in the blood of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…Our laboratory has evaluated PDT using the photosensitizer verteporfin in a number of immunologic test systems (8,10). Prolonged skin allograft acceptance (13), impaired adoptive transfer of autoimmune encephalomyelitis (26), prevention of adjuvant-enhanced arthritis (27), and inhibition of CHS (14) have been described for verteporfin-mediated PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has evaluated PDT using the photosensitizer verteporfin in a number of immunologic test systems (8,10). Prolonged skin allograft acceptance (13), impaired adoptive transfer of autoimmune encephalomyelitis (26), prevention of adjuvant-enhanced arthritis (27), and inhibition of CHS (14) have been described for verteporfin-mediated PDT.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, working with BPD, we observed that this photosensitizer could be activated (photobleached) in the circulation of mice if they were exposed to whole body illumination with red light under conditions that produced no observable skin photosensitivity. This procedure was termed transcutaneous PDT (15). Since then a number of studies have been undertaken to determine whether this "low level PDT" effect could influence immunological responsiveness with the thought that this could be a novel approach to the treatment of autoimmune diseases.…”
Section: Pdt-mediated Modulation Of Cell Behaviormentioning
confidence: 99%
“…Whole body transcutaneous photodynamic therapy was administered to unshaved miee with 80 J/em' light dose applied on day 0, 10, and 20 after arthritis induction. The optimal concentration of BPD and light dose necessary for cell killing was determined in preliminary studies [27].…”
Section: Clinical Eialuulionmentioning
confidence: 99%
“…Studies with this phoiosensitizer have shown lhat it is taken up selectively by activated lymphocytes (those bearing either the IL-2 receptor (IL-2R) or high levels of HLA-DR antigen) or other highly proliferative cells, thus rendering these populations susceptible to photodynamic destruction wilh 690-nm light [26]. Further, in recent experiments we demonstrated that BPD eotild be activated transdermally while in the circulation by exposure of animals to whole body illumination with red light [27]. These treatments resulted in photoactivation of between SQ% and 70% of circulating BPD.…”
Section: Introductionmentioning
confidence: 99%